Transformation of Prostitution Services and Stigma Against Prostitutes (WTS) : Literature Review - Mohamad Iqbal Tawakal; Johanna Debora Imelda (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
Advances in digital technology have encouraged prostitution service providers to transform from conventional prostitution to cyber prostitution by maximizing the use of information technology. This transformation also creates opportunities and threats for Prostitute Women (WTS) when they are active in the practice of the prostitution business. Although the vehicle for WTS practice has changed, the stigma against WTS continues to grow and is even more varied. This research explains comprehensively about the social environment of WTS; the growing stigma against WTS, the transformation of prostitution business services in the digital era, and how WTS's efforts to survive in the business. This article uses the literature review method. The results of this study found that in daily work activities, WTS often experience stigma and threats of violence from their surroundings and workplace. This stigma has resulted in the emergence of post-traumatic stress so that the mental health of WTS is disturbed and often feels afraid to face the surrounding environment. Another finding is that the transformation of prostitution services from conventional to cyber in fact does not reduce the stigma against WTS. Stigma against it is increasingly varied. Even so, WTS' drive to persist in cyber prostitution remains high. In fact, the work orientation of WTS in cyber prostitution is no longer just economic fulfillment, but to participate in the development of current trends. In order to survive in the transformed prostitution business, the social capital of WTS needs to be turned into a social security network for WTS to manage their stigma and minimize the threat of violence can naturally sustain cyber prostitution.